(untitled) (International Journal of Communication Systems and Network Technologies, 2022)
A rectangular patch is designed and simulated on CST studio suite software for wireless communication with slots cut out in the shape of “L”. It is designed on the operational frequency of 2.4 GHz. The design of the proposed antenna involves a rectangular patch and slots cut in the shape of “L” which indeed enhances the result. The antenna is the size of 60 mm x 60 mm x 1.6 mm and obtained peak gain of 6 dBi and maximum directivity of 6.40 dB at 2.4 GHz. The antenna achieves a radiation efficiency of 90% and a VSWR of less than 2 on the frequency of 2.4 GHz. As a result of its wide bandwidth, compact size, and stable radiation characteristics, so the proposed antenna is perfect for wireless communication.